Stock Price Dynamics and Firm Size: An Empirical investigation - CHEUNG, YIN‐WONG; NG, LILIAN K. (Journal of Finance, 1992)
ABSTRACT We show that after controlling for the effects of bid‐ask spreads and trading volume the conditional future volatility of equity returns is negatively related to the level of stock price. This “leverage effect” is stronger for small, as compared to large, firms. We also document that while the essential characteristics of the relations between stock price dynamics and firm size are stable, the strengths of the relationships appear to change over time.